Digitization As a Means of Shaping Power Potential And Socio-Economic Decisions - JANINA PACH (Communications of International Proceedings, 2025)
Access to Internet platforms is presented as a stimulator of the process of intensifying the division of liberal groups in society, working in favour of identity groups. Online service platforms serve as technical, political, and legal means to fight for economic interests and facilitate the emergence of self-sustaining communities, fenced off from others by the belief in a common identity. The social phenomena are approached through the example of the resistance of 2022 Ukraine in the face of Russia's military attack. The research problem is embedded in the assertion that access to digital services is one of the inclusive factors in institutions that has allowed a broad coalition to emerge as much as possible to lead the resistance against existing exploitation. The analysis is characterised by identifying the sources of power available to digitized operations, such as the creation of cryptocurrencies and other, to power the relevant state authorities, but also to induce the power of local communities. Legitimacy refers to power through the appropriateness of the outcomes of the operation and the fairness of the operation's practices.
Keywords: digital transformation; digital governance; empowerment of social groups; legitimization of power; war in Ukraine